Um estudo sobre regularidade de soluções de equações diferenciais parciais elípticas - Bezerra Júnior, Elzon Cézar (2016)
The main objective of this work is to study the regularity of solutions of elliptic partial differential equations of second order, will be used techniques such as the principle of maximum estimates a priori and the unequal Harnack. Finally generalize the solution concept seeking solutions in the Sobolev space W2, p((Ω).